2021: A Surface Odyssey. Role of Oxygen Functional Groups on Activated Carbon‐Based Electrodes in Vanadium Flow Batteries. Issue 24 (29th October 2021) - Radinger, Hannes
Abstract: The market breakthrough of vanadium flow batteries is hampered by their low power density, which depends heavily on the catalytic activity of the graphite‐based electrodes used. Researchers try to increase their performance by thermal, chemical, or electrochemical treatments but find no common activity descriptors. No consistent results exist for the so‐called oxygen functional groups, which seem to catalyze mainly the V III /V II but rarely the V V O2 + /V IV O 2+ redox reaction. Some studies suggest that the activity is related to graphitic lattice defects which often contain oxygen and are therefore held responsible for inconsistent conclusions. Activation of electrodes does not change one property at a time, but rather surface chemistry and microstructure simultaneously, and the choice of starting material is crucial for subsequent observations. In this contribution, the literature on the catalytic and physicochemical properties of activated carbon‐based electrodes is analyzed and evaluated. In addition, an outlook on possible future investigations is given to avoid the propagation of contradictions. Abstract : There is a lack of common activity descriptors to understand the fundamental reaction processes occurring on carbon‐based electrodes used in vanadium flow batteries. Most activation procedures do not change one property at a time but rather the surface chemistry and microstructure simultaneously. In this Minireview, selected literature on the electrochemical and physicochemical properties of treated electrodes is analyzed and an outlook on possible future investigations is provided.